WBP1L regulates hematopoietic stem cell function and T cell development - Krayem, Imtissal; Grusanovic, Srdjan; Duric, Iris; Pavliuchenko, Nataliia; Danek, Petr; Borna, Simon; Sekeresova Kralova, Jarmila; Skopcova, Tereza; Pokorna, Jana; Alberich-Jorda, Meritxell; Brdicka, Tomas (Frontiers in Immunology, 2024)
WW domain binding protein 1-like (WBP1L), also known as outcome predictor of acute leukemia 1 (OPAL1), is a transmembrane adaptor protein, expression of which was shown to correlate with ETV6-RUNX1 translocation and favorable prognosis in childhood leukemia. It has a broad expression pattern in hematopoietic and non-hematopoietic cells. Our previous work described WBP1L as a regulator of CXCR4 signaling and hematopoiesis. Here, we show that hematopoiesis in the mice with Wbp1l germline deletion is dysregulated, already at the level of hematopoietic stem cells and early progenitors. We further demonstrate that thymi of WBP1L-deficient mice are significantly enlarged and contain increased numbers of thymocytes of all subsets. This can potentially be explained by increased generation of multipotent progenitors 4 (MPP4) in the bone marrow, from which the thymus-seeding progenitors are derived. We also observed increases in multiple cell types in the blood. In addition, we show that WBP1L regulates hematopoietic stem cell functionality and leukocyte progenitor proliferation and gene expression during hematopoietic stem and progenitor cell transplantation, which contribute to more efficient engraftment of WBP1L-deficient cells. WBP1L thus emerges as a regulator of hematopoietic stem and progenitor cell function, which controls leukocyte numbers at the steady state and after bone marrow transplantation.